Development of organic reaction teaching model for pre-university programs in Malaysia - Abdulmalik, Sabitu (2022)
Previous theories and research have shown that collaboration between scholars and practitioners has far-reaching consequences for students’ learning. Therefore, bridging the lacuna between research and practice is necessary in the development and validation of an instructional model. The objective of this study is to develop and validate an organic reaction teaching model (ORTM) for pre-university programs in Malaysia based on the experts’ collective opinion. Given that matriculation colleges serve as entry points into universities, developing instructional models is beneficial. The focus on the organic reaction concept is due to its significance and centrality in many science-related subjects as a set of steps that explain the chemical changes that occur in organic compounds. Moreover, many students perceive organic reaction mechanisms as difficult concepts that serve as barriers to their understanding of advanced organic chemistry. This perceived difficulty makes organic reactions less appealing to students, leading to misconceptions and errors of serious concern. Thus, the in-depth information about students’ common errors and other challenges in organic chemistry instruction formed the basis of this study to develop a model for minimizing students' common errors and improving their academic performance in chemistry. Specifically, the research questions include: 1) To what extent is it necessary to develop ORTM to minimize common errors in organic reactions, based on the experts’ collective opinion? 2) What are the opinions of experts on the instructional activities and constructs to be included in the development of the ORTM? and 3) How does the ORTM help lecturers to improve students’ understanding of organic reaction mechanisms? The design and development research approach was adopted using an embedded mixed-method as the overall design of the study, so that one set of data plays a supporting or secondary role to the other data type coherently in the three phases of the study. The need for developing the model was justified in phase 1 through three sub-studies, i.e., scoping review, experts’ interviews, and analyses of students’ manuscripts. During this phase, an exploratory design was used, and data was collected qualitatively and analyzed using ATLAS.ti (version 8) software. Data source triangulation, peer debriefing, member checks, and audit trail were used to validate the findings. The second phase covered the design and development processes using exploratory mixed-method design. The main components of the model were identified qualitatively from literature and content analysis, pre-listed and presented to experts for scrutiny using the Delphi method. Quantitative data was obtained from 21 and 17 experts in two iterative Delphi rounds, respectively. Their views were analysed using the Inter Quartile Range (IQR), the Coefficient of Variance (CV), and the Kendall coefficient of concordance (W) at a consensus level of ≥75%. The ORT model was validated in phase three using an explanatory mixed design. The internal validity of the model was conducted to determine the suitability and usability of the model components using the fuzzy Delphi method (FDM). Qualitative data was collected using a fuzzy Delphi questionnaire from 14 experts purposively drawn from various related disciplines, and the external validity was conducted to determine the ORT model's practicability and potential in the actual classroom using the field-testing method (FTM) with five chemistry lecturers and 40 students from five matriculation colleges in Malaysia. Qualitative data was collected using an open-ended questionnaire, which was analysed using thematic analysis. Findings in phase one showed the variables studied, reasons for the difficulty of ORM, and students' common errors from the past literature. Analysis of the expert interviews revealed five themes indicating the significance of ORM, challenges in ORM instruction, teaching strategies adopted by the teachers, students' errors, and ways for improving ORM instruction. Also, failure to conserve charges, backward arrow positioning, the formation of hypervalent atoms, and missing arrows were the common errors identified from the analysis of students’ manuscripts. These findings stressed the need for developing an alternative model specifically for teaching organic reactions. The findings of phase two showed the developed model was comprised of 30 instructional activities, 5 instructional constructs including symbolisms, crosscutting, mechanisms, visualization, and refelection with mean ratings of (ꭓ = 25.00, 22.35, 21.76, 18.47, & 14.41) respectively, and 3 instructional domains for avoidance, interference, and correction with a mean rating of (ꭓ = 35.00, 33.53, & 31.47) at consensus level (W = 0.511, p<0.001) and a correlation in stability of rounds (rho = 0.41, p< 0.01). The mean ratings prioritized the domains and constructs for easy implementation of the model in the actual classrooms. Findings from phase three show that the model is valid as the fuzzy Delphi results indicated a consensual agreement on the suitability of the model components at a threshold value of 98.1% and defuzzification values of 13.20, 12.80, and 12.30 for the usability of instructional activities, instructional constructs, and domains, respectively. This indicates that the model components were consistently reliable for teaching to minimize students’ errors in ORM. In addition, findings from the field-testing method revealed that the model could be used in other settings, as expressed by the views of chemistry lecturers after implementing the model across the 5 matriculation colleges. Model compatibility, model clarity, model efficiency, and model flexibility themes indicate the practicability of the model in the classroom. The result also shows the potentiality of the model in minimizing students’ common errors in ORM and improving their academic performance at an overall average score of 84.4%. The findings from the need analysis phase provided a myriad view of the experts and the lacunae in organic chemistry instruction, which necessitates the development of an organic reaction teaching model. The model was developed in phase two, and the components were conceptually agreed upon by the experts. Also, both internal and external validity of the model were ensured in phase 3 of the study. Thus, the product of the study therefore removed the lacuna between research and practice, since practitioners, as the end users of the model, were fully involved in all the stages of the study. Furthermore, this study provides an instructional model as a guideline that helps teachers plan step-by-step lessons to minimize errors in ORM, and the domains of the model can be adopted in avoiding, interfering with, and correcting students’ errors. Also, the model components could simplify the planning and implementation of lessons in the classrooms and extend the comprehension of Johnstone's model in terms of explicit representation of organic reaction mechanisms from 3 to 5 levels. More importantly, ORTM integrated the principles of threshold concepts and repair learning theories into teaching to overcome students’ common errors in organic reactions. Moreover, the use of experts’ opinions in the design and development research approach adopted using Fuzzy Delphi and field-testing methods was crucial in curriculum and instruction. Finally, it is recommended for further studies to be conducted by stakeholders in the curriculum and instruction as well as the international science education community to plan, develop, validate, and implement alternative modules, e-learning tools, and measuring instruments based on ORTM components.